Gingival Curettage As An Adjunctive Non-Surgical Approach In Localized Chronic Periodontitis Of Tooth 43: A Case Report - Hanifah Ajeng Pangesti; Aprilia Yuanita Anwaristi (International Journal of Health Engineering and Technology, 2026)
Periodontitis is a chronic inflammatory disease that causes destruction of tooth-supporting tissues due to interactions between subgingival biofilm and the host immune response. This case report aimed to evaluate the effectiveness of gingival curettage as an adjunctive therapy in localized chronic periodontitis. A patient presented with complaints of swollen gingiva and bleeding during tooth brushing. Clinical examination revealed erythematous gingiva on tooth 43 with periodontal pocket depths of 3 mm mesiolabially, 2 mm midfacially, and 4 mm distolabially, along with an Oral Hygiene Index score of 3.3. Initial periodontal therapy consisting of scaling and root planing was performed, followed by gingival curettage due to persistent inflammation and positive bleeding on probing. Three weeks after treatment, periodontal healing was observed, characterized by negative bleeding on probing and reduced periodontal pocket depths to 2 mm at all examined sites. Gingival curettage can be considered an effective adjunctive treatment to eliminate inflammatory tissue, improve periodontal conditions, and enhance tooth prognosis when supported by optimal oral hygiene maintenance.